1985
DOI: 10.1097/00004032-198509000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Biometric Estimation of Chest Wall Thickness of Females

Abstract: Optimal use of whole-body counting data to estimate pulmonary deposition of many of the actinides is dependent upon accurate measurement of the thickness of the chest wall because of severe attenuation of low-energy x rays and photons associated with the decay of these radionuclides. An algorithm for estimation of female chest wall thicknesses, verified by real-time ultrasonic measurements, has been derived based on the correlation of measured chest wall thickness and other common biometric quantities. Use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

1988
1988
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…(571) Ultrasonic measurements have been used to determine chest wall thickness in studies such as those reported by Dean (1973), Fry and Summerling (1980), Summerling and Quant (1982), Berger and Lane (1985), Palmer et al (1989), Kruchten and Anderson (1990), Kang et al (1993), Vickers (1996, and Kramer et al (2001a,b). A number of factors have been shown to influence these measurements including the subject's height, body mass, age, and gender; whether the subject is in a sitting or supine position; and the size and location of the chest wall covered by radiation detectors for which chest wall thickness measurements are made.…”
Section: Specific Gravity Of Female Breast Tissuementioning
confidence: 99%
“…(571) Ultrasonic measurements have been used to determine chest wall thickness in studies such as those reported by Dean (1973), Fry and Summerling (1980), Summerling and Quant (1982), Berger and Lane (1985), Palmer et al (1989), Kruchten and Anderson (1990), Kang et al (1993), Vickers (1996, and Kramer et al (2001a,b). A number of factors have been shown to influence these measurements including the subject's height, body mass, age, and gender; whether the subject is in a sitting or supine position; and the size and location of the chest wall covered by radiation detectors for which chest wall thickness measurements are made.…”
Section: Specific Gravity Of Female Breast Tissuementioning
confidence: 99%
“…However, breast structures vary widely depending on multiple criteria like age, geographical origin, hormonal activity, corpulence, musculature, etc. Many studies (e.g., Berger and Lane 1985;Lee et al 2004) tried to identify reliable anthropometrical marks for quantifying and describing breast dimensions and developing empirical equations to determine breast shapes. The brassiere industry organizes measurement campaigns in order to produce the most representative bras fitting the most common sizes.…”
Section: Methodsmentioning
confidence: 99%
“…Lors de la création de la librairie de fantômes, la masse des seins a été reliée au tour de thorax et au bonnet en suivant les recommandations de spécialistes en chirurgie plastique et autres domaines connexes (Regnault et al, 1972 ;Berger et Lane, 1985 ;Smith et al, 1986 ;Pechter, 1998 ;Warren et al, 2007). Pour un tour de thorax donné, la taille de poitrine a été modifiée par l'ajout de la même quantité de tissu adipeux pour chaque changement de bonnet comme recommandé par Turner et Dujon (2005).…”
Section: Variation Du Bonnetunclassified